Effect of plant growth regulators on callus induction and Rutin production of Ricinus communis L. plant (Baghdad Science Journal, 2017)
Ricinus communis L. is an important medical plant hence it contains many active compounds. The aim of this research is to study the effect of plant growth regulators on callus induction and Rutin concentration. A combination of Benzyle adenine (BA) and Indol Acetic acid (IAA) at (0.0,1.0,2.0) mg/L was added to the media, the highest fresh weight of the induced callus from stem explant was (4.97) gr . at (1.0,1.0) mg/L BA and IAA consenquently the same combination gave the highest dry weight of callus (0.42) gr. while the combination at (2.0,1.0) mg/L BA and IAA gave the highest fresh weight of induced callus from Leaves explant (5.28) gr., then (2.0,1.0) mg/L BA and IAA gave the highest dry weight for callus induced from leaves at (0.55)gr.Spectrophotometer used to estimate rutin quantity and results showed that the present of rutin at (126.31) ppm in callus induced from stem at (2.0,2.0) mg/L BA and IAA, the highest value of this compound (121.05) ppm on callus induction from the leaves in the same combination as compared with Rutin quantity in intact plant that reached (94.73) ppm in leaves and (68.42) ppm in stem.